Configurable Hardware Architecture of Multidimensional Convolution Coprocessor - Geranun Boonyuu; Sumek Wisayataksin (My University, 2021)
We propose a configurable coprocessor for the convolutional neural network (CNN) that suit various models of CNN. It can operate 2D standard convolution, 2D depthwise separable convolution, 3D convolution, and a fully connected layer. The proposed processing cluster consists of 72 processing units (PUs) of half-precision floating-point to assist the main processor in embedded systems. The experimental results on Artix-7 FPGA revealed that our design has 12.16 GOPs per cluster. Moreover, this architecture was designed to be scalable for the systems with higher performance.
Keywords: Advanced Neural Network Applications; Advanced Vision and Imaging; Advanced Image and Video Retrieval Techniques